2019
DOI: 10.1177/0038026119881093
|View full text |Cite
|
Sign up to set email alerts
|

Money, power, and inequality within marriage among Palestinian families in Israel

Abstract: A key factor in promoting egalitarian gender relations is financial independence for women. Palestinian women citizens of Israel (PWCI) serve as a case study for gender relations in a patriarchal society. The financial identity of these women develops alongside general institutional discrimination, dual judicial systems (civil and religious), civil status, and cultural norms. However, factors affecting family budget allocation and financial autonomy of women in this society are not well understood. The present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Another related possible explanation is that marital satisfaction is a proxy for women's dependency on their husbands in matters related to parental capacity. A recent study found that the financial independence of Arab women in Israel is limited, reflecting the unequal gender and power relations of Arab society [43]. It could be that the women's high degree of marital satisfaction reflected their ability to maintain a good relationship with their husbands and hence greater access to the family's financial means, enabling them to more successfully execute the variety of tasks involved in parenting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another related possible explanation is that marital satisfaction is a proxy for women's dependency on their husbands in matters related to parental capacity. A recent study found that the financial independence of Arab women in Israel is limited, reflecting the unequal gender and power relations of Arab society [43]. It could be that the women's high degree of marital satisfaction reflected their ability to maintain a good relationship with their husbands and hence greater access to the family's financial means, enabling them to more successfully execute the variety of tasks involved in parenting.…”
Section: Discussionmentioning
confidence: 99%
“…The study also did not examine differences between various ethnic groups within the Arab population. The Arab population comprises Muslims, Christians who are considered less traditional and more urbanized than their Muslim counterparts, and Druze, a very religious and conservative community that resides mainly in rural villages in northern Israel [43]. Because the latter two groups were a very small part of the sample (7.6% and 14.7%, respectively), we were unable to consider them separately and included them in the larger Arab group.…”
Section: Limitations and Future Studies Directionsmentioning
confidence: 99%
“…Arab society is considered patriarchal (Abu‐Baker, 2016; Meler, 2020). Despite, for example, that women can currently pursue higher education, the family structure and gender roles of Arab Israeli families remain essentially unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…Another type of economic abuse is related to income allocation, i.e., decisions about and practices of how the money generated by household members is divided between areas of expenditure and savings (Meler, 2019). The outcome of these decisions and practices is considered the actual income distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of these decisions and practices is considered the actual income distribution. Income is allocated through overt and covert mechanisms operating within the household (Pahl, 1983; Vogler, 1994), based on different gender expectations (Meler, 2019; Roman & Vogler, 1999). Different methods of money management between spouses are clearly related to income, and gender inequalities in access to money are a result of these allocation systems (Roman & Vogler, 1999).…”
Section: Introductionmentioning
confidence: 99%